Extrinsic conditions for the occurrence & characterizations of self-healing polyurea coating - Choo, Wan Luoh (Nanyang Technological University, 2021)
Metal structures and polymers are susceptible to corrosion and degradation, which affect their mechanical properties, resulting in material failure. Protective coatings have been used widely to provide protection against corrosion and degradation caused by reaction in the presence of moisture and oxygen. However, because the maintenance and re-coating process of large ships and pipelines underwater are particularly difficult, there is still room for improvement in the role of the conventional coating. In addition, self-healing polyurea coating is gaining extensive attention due to its superior properties whereby manual maintenance is not required. Organic coating with microencapsulated drying oil as the healing agent has been extensively studied for its self-healing ability in air (atmospheric oxygen) but the study on its self-healing ability in water (dissolved oxygen) is still lacking.